Review Of Islamic Law To The Use Of Article 28 Subsection 2 About Speech Hatred And Defamation (UU Number 19 AT 2016 Amendments to UU Number 11 at 2018) - Arbanur Rasyid (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2019)
Hate Speech  has recently become a warm conversation, not only in the media, but has begun to be discussed in scientific forums as a result of the many characters who are ensnared by hate speech due to making uploads in Social Media that is considered insulting to other people or state institutions by making a statement containing elements of hate speech in accordance with the criminal threat in Article 28 paragraph 2 of Law number 19 of 2016 amendment to law number 11 of 2008. Long before the law talks about hate speech, Islam through the Qur'an speaks a lot about how God denounces the actions of people who insult, berate, speak ill of others and make hoaxes, and Allah threatens sin for those who do it . Even in the history of Islam through the Prophet Muhammad had given a caning to people who make hoaxes, and the sentence in the Islamic criminal law is called Ta'zir, thus Islam is very careful and highly respects the human rights of a person including in protecting the soul and someone's honor